Proposed Marketing Strategy For PR FM To Increase National Advertising Sales - Hilman, Tamadara; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2015)
Abstract. Mass media has its function to fulfill people's needs for information and news. One of the well-developed mass media in Indonesia is radio. See the business development in radio industry, PT Mustika Parahyangan established a news radio with citizen journalism based-concept named PR FM. Since it was established in 2009, PR FM showed positive revenue progress. Revenue is derived from advertising sales, which divided into two categories, national and local advertising. One problem faced by PR FM is lack of national advertising sales. In 2013, national advertising only contributed for 2% of total revenue, while national advertising provides greater profits for the company than local advertising. This study is conducted in order to find the right marketing strategy to increase national advertising sales. To determine the root causes that lead to business issues, it needs more focused analysis of both external and internal situation. This study uses PEST, Porter's 5 Forces and competitor analysis to determine the external conditions that may affect the performance of business in the radio industry. While the internal conditions examined by using analysis of revenue stream to determine differentiated revenue, customer analysis and marketing mix analysis. This research used interview, observation (ethnographic), study documentation and internet study to collecting the data.The analysis resulted that PR FM too focused in increasing the number and loyalty of listeners. While the lack of national advertisers may due to the lack of segmentation, targeting and positioning which are focused to advertisers. PR FM does not approach the advertisers as part of consumers who provide direct financial benefits.In addressing these issues, this study aims to provide business solutions for PR FM. Business solutions consist of STP and 7P Marketing Mix proposals which focused on human resources and promotion performances. There is also implementation plan for PR FM to implement the proposed business solution that consists of marketing mix implementation plan, budgeting plan and timeline activities implementation plan.Keywords: mass media, radio industry, national advertising, PR FM, marketing strategy, STP, marketing mix.